Navigating Diagnostic and Treatment Decisions in Non‐Small Cell Lung Cancer: Expert Commentary on the Multidisciplinary Team Approach. (21st November 2020) - Popat, Sanjay; Navani, Neal; Kerr, Keith M.; Smit, Egbert F.; Batchelor, Timothy J.P.; Van Schil, Paul; Senan, Suresh; McDonald, Fiona
Abstract: : Non‐small cell lung cancer (NSCLC) accounts for approximately one in five cancer‐related deaths, and management requires increasingly complex decision making by health care professionals. Many centers have therefore adopted a multidisciplinary approach to patient care, using the expertise of various specialists to provide the best evidence‐based, personalized treatment. However, increasingly complex disease staging, as well as expanded biomarker testing and multimodality management algorithms with novel therapeutics, have driven the need for multifaceted, collaborative decision making to optimally guide the overall treatment process. To keep up with the rapidly evolving treatment landscape, national‐level guidelines have been introduced to standardize patient pathways and ensure prompt diagnosis and treatment. Such strategies depend on efficient and effective communication between relevant multidisciplinary team members and have both improved adherence to treatment guidelines and extended patient survival. This article highlights the value of a multidisciplinary approach to diagnosis and staging, treatment decision making, and adverse event management in NSCLC. Implications for Practice: This review highlights the value of a multidisciplinary approach to the diagnosis and staging of non‐small cell lung cancer (NSCLC) and makes practical suggestions as to how multidisciplinary teams (MDTs) can be best deployed at individual stages of the disease to improve patient outcomes and effectively manage common adverse events. The authors discuss how a collaborative approach, appropriately leveraging the diverse expertise of NSCLC MDT members (including specialist radiation and medical oncologists, chest physicians, pathologists, pulmonologists, surgeons, and nursing staff) can continue to ensure optimal per‐patient decision making as treatment options become ever more specialized in the era of biomarker‐driven therapeutic strategies. Abstract : This article highlights the value of a multidisciplinary approach to diagnosis and staging, treatment decision making, and adverse event management in non‐small cell lung cancer.